Sea Surface Temperature Mapping at Medium Scale Using Landsat 8 -TIRS Satellite Image - Lalu Muhamad Jaelani; Adillah Alfatinah (Institut Teknologi Sepuluh Nopember, 2017)
The Sea Surface Temperature (SST) retrieval from satellites data has been available since 1980’s both temporally and spatially. Some researchers have established SST inversion models depending on the correlation between the TM/ETM+ TIR radiance and the in-situ data. The objective of this research is to evaluate the performance of Landsat 8-estimated SST from 4 existing algorithms: Planck, Mono-Window Algorithm (MWA), Syariz and Split Window Algorithm (SWA) algorithms on 4 different tested areas: Eastern Bali, Bangkalan, Bombana and Poteran waters. Algorithm of Syariz dan SWA produced acceptable accuracy on all tested area with the NMAE ranged at 0.2-19.6% and 3.4-9.9% for Syariz and SWA, respectively. However, MWA and Planck produced NMAE larger than 30% on Bali and Poteran waters. Following the successful of SWA algorithm, the same algorithm was developed using insitu data collected on Poteran waters. The estimated SST by the developed algorithm produced acceptable accuracies on all tested water areas with the NMAE ranged from 0.401% to 16.630%. It was indicated that Syariz, SWA and the developed algorithms were applicable for SST retrieval on all tested waters